Influences of the Work Environment on Nurses’ Psychological Wellbeing at Selected Teaching Hospitals in Lusaka, Zambia: A Focus on Secondary Traumatic Stress and Burnout (International Journal of Scientific Research and Management (IJSRM), 2025)
Introduction: The current study sought to establish associations of the nurse work environment, with Secondary Traumatic Stress and Burnout among nurses at selected Teaching Hospitals in Lusaka, Zambia. Methods: A correlational study was conducted at three Teaching Hospitals in Lusaka, Zambia using a stratified sample of 250 nurses. Spearman rank order correlations and hierarchical linear regression were employed to determine correlations among variables at 95% confidence level and 0.05 level of significance. Results: Secondary Traumatic Stress was positively correlated with levels of nursing workload (rs = .18, p<.004) and level of stress reported between respondents and their supervisors (rs = .20, p = .001). Taken together, quality of the respondent’s relationship with the supervisor and the reported level of nursing workload explained 23.7% of the variance in Secondary Traumatic Stress [F (5, 244) = 4.793, p < 0.001, R2 = 0.237]. Reported quality of relationship with the supervisor and reported level of nursing workload also explained 12.1% of the variance in Burnout [F (5, 244) = 6.748, p < 0.001, R2 = 0.121]. Conclusion: Findings of this study suggest a need to develop measures that can enhance good relationships between nurses and their supervisors, reduce nursing workloads and regulate frequency of exposure to severe patient suffering.